Pengaruh Terapi Murottal Terhadap Depresi Pada Pasien Congestive Heart Failure Di Pusat Jantung Terpadu RSUP Dr. Wahidin Sudirohusodo - Harisa, Akbar; Wulandari, Putri; Ningrat, Syahrul; Yodang, Yodang (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Congestive Heart Failure can have a psychological impact on a patient's life. The effect ofthe psycologicalimpact which commonly found is depression. Murottal Al-Qur'an therapy is one type of nonpharmacological treatment used to reduce depression because it can cause a relaxation response for thosewho listen to it. This study aims to determine the effect of Murottal therapy on depression scores inCongestive Heart Failure patients at the Integrated Heart Center Dr. Wahidin Sudirohusodo. Thisresearch method was a type of Quasi-experimental research with the research design used is Time SeriesWith Control Group Design. Thirty-six respondents were divided into two groups. Each group was 18respondents. The instrument used was the Hamilton Anxiety and Depression Scale questionnaire. Datawere analyzed using the Wilcoxon test. The results of this study obtained a value of p <0.05. This meansthat in general, there was the influence of murottal therapy interventions on depression. The conclusionwas murottal Al-Quran therapy can reduce depression in Congestive Heart Failure patients. Therefore,care providers were expected to provide nursing interventions using Al-Quran reading as a complementarytherapy to reduce depression scores